The Unanticipated Catalytic Activity of Lithium tert-Butoxide/THF in the Interesterification of Rapeseed Oil with Methyl Acetate - Valdis Kampars; Zane Abelniece; Sabine Blaua (Journal of Chemistry)
Conventionally, the biodiesel (mixture of fatty acid methyl esters, FAME) production proceeds by transesterification of triglycerides with methanol accordingly by the formation of glycerol as a by-product, which cannot be included in biofuel composition. Biodiesel could also be produced via interesterification ensuring full conversion of oil to biofuel, consisting of FAME and triacetin. The most effective catalysts for interesterification reactions are alkali metal alkoxides. The effectivity of alkoxide catalyst depends on its solubility determined by the structure of the alkyl chain. In our previous studies, we have shown that the branched chain catalyst tert-BuOK/THF is highly suitable for the realisation of interesterification reactions. Till now, in the scientific literature, very little is known about the influence of metal ions. In order to investigate the influence of counterion on the activity of alkoxide catalysts, in this work, we have investigated the proceeding of interesterification reactions of rapeseed oil with methyl acetate in the presence of lithium, sodium, and potassium tert-butoxides in THF. Experimentally obtained relationships for catalyst-to-oil molar ratio (COMR) influence rapeseed oil interesterifications with methyl acetate at 55°C for 1 h, with methyl acetate-to-oil molar ratio (MAOMR) 18 showing that the tert-BuONa/THF and tert-BuOK/THF have high and similar activity, but the tert-BuOLi/THF is fundamentally different. The low and diverse activity of lithium tert-butoxide can be explained by the association of ions and very low catalytic activity of ion pairs. Simulation of the influence of association on the FAME formation shows that at COMR 0.1 (sufficient for fast reaction proceeding in the presence of tert-BuONa/THF and tert-BuOK/THF), the concentration of tert-butoxide ions in the presence of tert-BuOLi/THF because of associations lowers from 28 mmol/L to 13 mmol/L, whcih is not sufficient for effective proceeding of reaction. Activity of alkoxides in this reaction is solely determined by the counterion.